Por um “arquivo vivo”: uma abordagem decolonial à coleção do Centro de Arte Moderna da Fundação Calouste Gulbenkian - Filipa Coimbra (Midas: Museus e Estudos Interdisciplinares)
This article aims to situate the importance of the archive in the decolonization of museums and their collections through technological, discursive and museological perspectives. Taking the Modern Art Centre (CAM) collection of the Calouste Gulbenkian Foundation (FCG, Lisbon) as a case-study and Gulbenkian archives as a resource, the development of CAM’s collection during the final stage of the Portuguese colonial empire will be examined. To this end, I draw on unpublished data about the acquisition of two sets of artworks acquired in Mozambique and Angola by then Foundation's chairman, José de Azeredo Perdigão (1896-1993). These acquisitions occurred in the context of his official journey to these two African territories in 1963, which were under Portuguese colonial rule at the time. I will analyse the collecting processes of these artworks, by questioning their absence from the collection, institutional narrative and exhibitions. In the context of the collection's and the institution's histories, issues such as the autonomy and neutrality of the FCG vis-à-vis the Portuguese dictatorship (and its colonial policy) will also be under review. In this way and framed in the recent focus on collections and the responsibility of museums in recognizing persistent historical omissions, I will seek to highlight a poorly known (and problematic) period in the history of one of the most important modern and contemporary art collections in Portugal, in contrast with the period after its musealization, in 1983.